Waveform Decontamination for Improving Satellite Radar Altimeter Data Over Nearshore Area: Upgraded Algorithm and Validation - Wang, Haihong; Huang, Zhengkai (Frontiers in Earth Science, 2021)
One of the thorniest problems in altimetry community is retrieving accurate coastal sea surface height(SSH), especially in the last several kilometers offshore. It is confirmed in previous studies that decontaminating waveforms is beneficial to improve the quality of coastal SSHs. In this paper, we proposed an upgraded strategy for waveform decontamination, including a novel realignment algorithm and gate-wise outlier detector. We validated the new strategy in four test regions using Jason-2 altimeter data. In the validation process, we compared retracked SSHs by 16 retrackers, which include retrackers provided in SGDR(Sensor Geophysical Data Record), ALES (Adaptive Leading Edge Subwaveform) and PISTACH (Prototype Innovant de Système de Traitement pour les Applications Côtières et l’Hydrologie) products. Comparison results verified that retracking the waveforms decontaminated using our new method can greatly improve the SSHs in coastal region. The 20% threshold retracker(DW-TR20) and the ICE1 retracker(DW-ICE1) based on the decontaminated waveforms outperform other retrackers, especially in 0-4 km zone offshore. DW-TR20 and DW-ICE1 can provide robust SSHs with a consistent accuracy in 0-20 km coastal band and a high correlation (>0.9) with nearby gauge data. To conclude, the upgraded waveform decontamination strategy provides a promising solution for coastal altimetry, which makes it possible to extend reliable observations to the last several kilometers offshore.